phonetics and phonology of Eastern Andalusian Spanish: a review of literature from 1881 to 2016 - Herrero de Haro, Alfredo (Íkala, Revista de Lenguaje y Cultura, 2017)
Despite previous studies on Eastern Andalusian Spanish, interest on this geolect boomed only after the theory of vowel doubling was posited for this variety of Spanish. According to this theory, in Eastern Andalusian Spanish, vowels preceding /s/ aspiration or deletion change their quality, thus, carrying the semantic function of /s/. Since then, many researchers have studied the vowel and consonant systems of this variety of Spanish and the phonetic-phonological debate is still ongoing. This article reviews the main studies on Eastern Andalusian Spanish pronunciation between 1881 and 2016, comparing the different findings in that period and summarising them chronologically. The article finishes with an outline of widely accepted and debated features of Eastern Andalusian Spanish in order to identify future lines of research.